KGB propaganda actions against political activity of lithuanians émigré in 1970s–1990s. - Burinskaitė, Kristina (Genocidas ir rezistencija, 2009)
One of the main tasks of Lithuanian KGB was to weaken, discredit and suppress political activity of Lithuanian émigrés to liberate Lithuania, to change their attitude toward Soviet Lithuania. Propaganda, the formation of positive public opinion about the Soviet system, politics, achievements and a negative opinion about émigrés were one of the main weapons against the political activity of émigrés. To form such public opinion, the KGB used mass media, tourism, and the Lithuanian language and literature courses at Vilnius University, science exchange, cultural activity, tours of Lithuanian artists to Western countries. Speeches of famous Lithuanians (some of them were forced to speak positively about Soviet achievements) and émigrés were also used by the Soviets as a means of propaganda. The return of the valuables of art was also used as propaganda, to set at variance the émigrés and to break their isolation policy toward Soviet Lithuania. Propaganda actions were politicized and used against the émigrés, since the time of their implementation coincided with the important émigrés events. KGB developed wide propaganda actions against the world Lithuanian youth congress and the Baltic cruise of freedom and peace. It is difficult to evaluate the effectiveness of KGB actions due to the lack of objective sources. Although KGB paid great attention to propaganda activity, the results, however, were inadequate to their efforts.